2020
DOI: 10.1111/aos.14540
|View full text |Cite
|
Sign up to set email alerts
|

Differences in outflow channels between two eyes of unilateral primary congenital glaucoma

Abstract: Purpose Primary congenital glaucoma (PCG) occurs in only one eye in some patients. We aimed to characterize anatomical features of the angle and Schlemm’s canal (SC) in vivo among fellow eyes of patients with unilateral primary congenital glaucoma. Methods Both eyes of 33 children with unilateral PCG and 30 healthy, age‐matched children, old enough to co‐operate were analysed using high‐resolution anterior segment spectral domain (SD) OCT. Subgroup analysis was done for the presence/absence of angle dysgenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…In a previous study, we have also shown that SC can open backward into the intracameral space both on in vivo imaging as well as on histopathology in fellow eyes of congenital glaucoma. 10 Similar opening of SC intracamerally was seen in 2 eyes post ACP (Fig 2c Post), suggesting another route of clearing for corneal edema.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 60%
“…In a previous study, we have also shown that SC can open backward into the intracameral space both on in vivo imaging as well as on histopathology in fellow eyes of congenital glaucoma. 10 Similar opening of SC intracamerally was seen in 2 eyes post ACP (Fig 2c Post), suggesting another route of clearing for corneal edema.…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 60%
“…[ 33 34 ] We have shown that SD-OCT scans can successfully capture the anterior angle at high resolution and may help in identifying angle dysgenesis in cases where angle anomalies are subtle enough to go unnoticed. Although identifying gross dysgenesis of the angle, as in PCG may be easier,[ 35 ] subtle angle anomalies as in JOAG or POAG are more challenging to identify. The biological changes in the extracellular matrix (ECM) comprising the trabecular drainage pathways that lead to IOP elevation have been identified in histopathological studies[ 36 37 ] in POAG.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our previous study also demonstrated that the SC can open directly into the anterior chamber, both on in vivo imaging and histopathology. 5 While this is a small series, our observations offer an alternative mechanistic explanation for the instantaneous clearing of corneal oedema post-ACP, which requires further support from experimental studies.…”
mentioning
confidence: 81%